1996
DOI: 10.1002/(sici)1099-0992(199601)26:1<15::aid-ejsp729>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Observational evaluative conditioning of an embedded stimulus element

Abstract: Evaluative conditioning refers to the observation that the mere pairedpresentation of a neutral stimulus (CS) with a liked or disliked stimulus (US) may result in the neutral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…In EC, the preference for a stimulus, the CS, is changed due to pairing with another liked or disliked stimulus, the US (Hofmann, De Houwer, Perugini, Baeyens, & Crombez, 2010). It has also been shown that such changes in preferences can occur following observation of another individual exposed to the CS-US contingency and expressing liking or disliking the US (Baeyens, Kaes, Eelen, & Silverans, 1996;Baeyens, Vansteenwegen, De Houwer, & Crombez, 1996). However, EC lies beyond the scope of this thesis and will therefore not be discussed further.…”
Section: Extinctionmentioning
confidence: 99%
“…In EC, the preference for a stimulus, the CS, is changed due to pairing with another liked or disliked stimulus, the US (Hofmann, De Houwer, Perugini, Baeyens, & Crombez, 2010). It has also been shown that such changes in preferences can occur following observation of another individual exposed to the CS-US contingency and expressing liking or disliking the US (Baeyens, Kaes, Eelen, & Silverans, 1996;Baeyens, Vansteenwegen, De Houwer, & Crombez, 1996). However, EC lies beyond the scope of this thesis and will therefore not be discussed further.…”
Section: Extinctionmentioning
confidence: 99%
“…These modelling effects have also been observed in humans. In one study, children drank different flavours of new drinks while watching a video of a model expressing a like or dislike of the same drink (Baeyens et al , 1996). The children were found to prefer the flavour that the model had liked.…”
mentioning
confidence: 99%
“…Unreinforced CS presentations, after acquisition, do not affect the acquired CS valence, whereas conditioned skin conductance responses generally disappear after a sequence of CS-alone presentations~Öhman, 1983!. This phenomenon is especially true when the electrodes for delivery of the US are removed and the participants are instructed that there will be no more USs~Hugdahl & Öhman, 1977!. A second argument was that explicit verbal knowledge of the CS-US contingency or contingency awareness does not seem to be required for evaluative conditioning~Baeyens, Eelen, & Van den Bergh, 1990;Baeyens, Kaes, Eelen, & Silverans, 1996;Baeyens, Wrzesniewski, et al, 1996;Hammerl & Grabitz, 1996!. This argument is in sharp contrast with what is observed in conditioning of orienting0preparatory responses: for example Dawson and Schell 1987!…”
mentioning
confidence: 99%